Toward Human Models of Cardiorenal Syndrome in vitro - Gabbin, Beatrice; Meraviglia, Viviana; Mummery, Christine L.; Rabelink, Ton J.; van Meer, Berend J.; van den Berg, Cathelijne W.; Bellin, Milena (Frontiers in Cardiovascular Medicine, 2022)
Abstract Heart and kidney diseases cause high morbidity and mortality. Heart and kidneys have vital functions in the human body and, interestingly, reciprocally influence each other’s behaviour: pathological changes in one organ can damage the other. Cardiorenal syndrome (CRS) is a group of disorders in which there is combined dysfunction of both heart and kidney but the underlying biological mechanisms of CRS are not fully understood. This is because complex, multifactorial, and dynamic mechanisms are likely involved. The consequence is that effective treatments are currently unavailable but this may be resolved if more was known about how the disease develops and progresses. To date, CRS has actually only been modeled in mice and rats in vivo. Even though these models can capture cardiorenal interaction, they are difficult to manipulate and control. Moreover, interspecies differences may limit extrapolation to patients. The questions we address here are what would it take to model CRS in vitro and how far are we? There are already multiple independent in vitro (human) models of heart and kidney but none have so far captured their dynamic organ-organ crosstalk. Advanced in vitro human models can provide an insight in disease mechanisms and offer a platform for therapy development. CRS represents an exemplary disease illustrating the need to develop more complex models to study organ-organ interaction in-a-dish. Human induced pluripotent stem cells in combination with microfluidic chips are one powerful tool with potential to recapitulate the characteristics of CRS in vitro. In this review, we provide an overview of the existing in vivo and in vitro models to study CRS, their limitations and new perspectives on how heart-kidney physiological and pathological interaction could be investigated in vitro for future applications.